ANALISIS DETERMINAN VOLUME PERDAGANGAN SUKUK NEGARA RITEL SERI SR-007 - Ni'mah, Laily Farikhatun; Pratomo, Ahmad Sidi (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2019)
Trading volume of retail sukuk is the number of sheets of the State retail sukuk listed on the stock exchange. The country's retail sukuk issued to finance a deficit Budget of income and Expenditure of the State (STATE BUDGET) the purpose of this research is to examine and analyze the influence of internal factors and external factors against a trading volume of sukuk country retail series SR-007. This research uses descriptive kuantitaif approach. Researchers use the data monthly April 2015 period until March 2018. The variables used in this study is the price, the Yield to Maturity (YTM), exchange rates, For the results of Mudharabah Deposits, the BI rate, inflation and trading Volume of Sukuk Retail Series SR-007. The research analytical tool is Vector Error Correction models (VECM) using Eviews 9. The results of this research show that there is a short-term relationship between variables that influence positive YTM against trading volume of sukuk retail series SR-007. In a long term relationship variables YTM, the exchange rate, the BI Rate, and inflation provide a positive influence against the trading volume of sukuk retail series SR-007. Variable YTM on long term negative effect against the trading volume of sukuk retail series SR-007.